OBJECTIVE METHODS FOR DETERMINE THE SEVERITY AND PROGNOSIS OF PERINATAL HYPOXIC-ISCHEMIC CNS - D. V. Blinov (Акушерство, гинекология и репродукция, 2016)
Perinatal hypoxic-ischemic damage of the CNS is a major cause of mortality and neonatal incapacitating. The severity and prognosis is not always possible to accurately determine by clinical and tools methods of examination. Neurospecific proteins (NSP) could be as markers of pathological processes. One of the most studied among the NSP are gliofibrillary acid protein - GFAP, a structural protein of intermediate filaments of astrocytes, and neuron-specific enolase - NSE, neuronal cytoplasmic glycolytic enzyme that catalyzes the conversion of 2-phosphoglycerate to 2-phosphoenolpyruvate. Investigation of the NSP concentration in the serum could be useful to evaluate the resistance of the BBB, determining the severity of CNS damage and prognosis for a disease in children with perinatal hypoxic-ischemic damages of the CNS.